The Effectiveness of Imagery Training on Enhancing Mental Focus in Pencak Silat Athletes - Ayu P, Dhayinta Bening; Astuti, Dessita Maharani; Salsabila, Khansa Naila Hana; Susanti, Ruth Natalia; Mayangsari, Dewi (Yayasan Sinergi Kawula Muda, 2025)
This research aims to explore the effectiveness of imagery training in increasing the focus of pencak silat athletes. Mental focus is a crucial element in sports performance, because good mental readiness can influence the outcome of a match. This study used an experimental design with the subject an athlete with the initials SA who was known to have difficulty maintaining focus when competing. The imagery training was carried out over two sessions, and its effectiveness was evaluated through pre-test and post-test measurements. The research results showed a significant increase in athletes' ability to focus after participating in imagery training. This finding is in line with previous research which states that imagery techniques can be an effective tool in training athletes' mental focus.